The expression of CD74 and macrophage migration inhibitory factor protein is upregulated in hepatitis B virus-related hepatocellular carcinoma - Lu, Mingzhu; Xu, Yun; He, Guangzhao; Liu, Qian; Zhu, Jing; Zhang, Changsong (Translational Cancer Research, 2018)
Background: Pro-inflammatory cytokine production, such as CD74 and macrophage migration inhibitory factor (MIF) could play an important role in liver cancer following chronic hepatitis B virus (HBV) infection. Methods: The level of CD74 was evaluated by using a capture enzyme-linked immunosorbent assay (ELISA) kit. The level of MIF protein was determined using Human Magnetic Luminex® Assays on 60 HBV-related hepatocellular carcinoma (HCC) patients. The level of HBV copies was determined by using real-time polymerase chain reaction (RT-PCR). Furthermore, α-fetoprotein (AFP), alanine aminotransferase (ALT), and aspartate aminotransferase (AST) were determined by the cobas 6000 analyzer. Results: The mean concentration of CD74 was elevated significantly in the tumor tissues (10.24 ng/mg) when it was compared with non-tumor tissues (3.86 ng/mg). Meanwhile, the level of MIF was 63.49 ng/mg in the tumor tissues, and 45.47 ng/mg in non-tumor samples. We found that elevated CD74 protein expression was associated with an elevated serum AFP level and the AST/ALT ratio; however, an elevated MIF protein level was associated with a lymph node metastasis, serum AFP level and AST/ALT ratio. Only a high level of MIF protein was associated with a short-term survival rate of just months in the HBV-related HCC patients. The elevated expression of MIF protein was associated with HBV ≥105 (copies/mL) in liver cancer. The elevated level of MIF protein was associated with the elevated level of CD74 protein in HBV-associated HCC progression. Conclusions: These results suggest that the elevated level of CD74 and MIF cytokines could play a significant role in HBV-related HCC.